A Work study on S&J Industries Incorporated (Plastics Division) - Lacson, Francis L. (College of Engineering, 1992)
S&J is a job shop form of production system that produces hundreds of varieties of products for a number of customers. The main factory contains a Plastics division, a Metals division, and a Tool and Die division. The PMP (Plastic Moulding Plant) is the part of S&J that produces the plastic products. Documentation of the PMP system includes descriptions of both the PMP area and the FAS (Final Assembly) area. The next documentation is that of a sample of 6 products selected, tracing their movement from injection moulding to final assembly. Final documentation is about the present system, where it was studied and analyzed. A number of minor problem areas where identified and documented, but the major problems were seen when looking at the system as a whole, and seeing how the subsystems communicated with each other.